Tożsamość kulturowa w wykładni i stosowaniu prawa administracyjnego - Zirk-Sadowski, Marek (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
The objective of the paper is a rough sketch of the process of development of cultural identity inside of the Polish administrative law. Interpretation of the public law in the country which finished process of transformation after the collapse of communist regime has a lot of difficult moments. Uncertain scopes of constitutional meanings and gaps in the set of legal principles are neutralized by the tendency among lawyers to identify with European legal culture and its values. The author of the text is deeply convinced that there is a need for legal version of the cultural identity based on European values. The paper comprises the concept of such identity in so called narrative version and descriptions of the development of the identity in the Polish judicial application of administrative law.